การพัฒนาทักษะการให้คำปรึกษากลุ่มของครูในโรงเรียน โครงการกองทุนการศึกษาจังหวัดอุตรดิตถ์ - ปัญญาใส, วจี (Ph.D. in Social Sciences Journal, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อวัดทักษะการให้คำปรึกษากลุ่มของครูในโรงเรียน โครงการกองทุนการศึกษาและศึกษาประสิทธิผลของการพัฒนาทักษะการให้คำปรึกษาของครูในโรงเรียนโครงการกองทุนการศึกษา โดยใช้การวิจัยกึ่งทดลอง (Quasi experiment) แบบ One group Pretest Posttest Desing กลุ่มตัวอย่างที่ใช้ในการวิจัย ได้แก่ ครูในโรงเรียนโครงการกองทุนการศึกษา 3 โรงเรียน จำนวน 15 คน โดยการเจาะจงจากครูผู้ทำหน้าที่แนะแนว ครูประจำชั้น ครูหัวหน้าระดับ และครูฝ่ายปกครอง ผลการวิจัย พบว่า ผลการวัดทักษะการให้คำปรึกษาของครูกลุ่มตัวอย่าง จำนวน 15 คน คะแนนก่อนการทดลอง มีค่าเฉลี่ย 16.93 และเมื่อเข้าร่วมโครงการเพื่อพัฒนาทักษะการให้คำปรึกษากลุ่มแล้ว กลุ่มตัวอย่างมีคะแนน ของการวัดทักษะการให้คำปรึกษาเฉลี่ย 20.67 แสดงว่าครูกลุ่มตัวอย่างมีทักษะการให้คำปรึกษากลุ่มเพิ่มขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 THE DEVELOPMENT OF GROUP COUNSELING SKILLS FOR TEACHERS IN FUND EDUCATION SCHOOLS UTTARADIT PROVINCE The purpose of this study was measurement group counseling skills and Effectiveness of development teachers counseling skills in fund education schools. The subject were purposive sampling of 15 teachers from 3 schools of the fund education schools, composes of the guidance teacher, class teacher, head of the class teacher and parents teacher, for the Quasi experimental research, One group Pretest Posttest Desing. The result of the study showed that, the subject is average pretest score was 16.93 and the average posttest was 20.67. The score were significantly increasing than before the experiment at .05 level. The effectiveness after the completion of the study was higher than prior to the study.